The E3 ubiquitin ligase MuRF2 attenuates LPS‐induced macrophage activation by inhibiting production of inflammatory cytokines and migration. Issue 2 (8th January 2018) - Bian, Hongjun; Gao, Shanshan; Zhang, Di; Zhao, Qi; Li, Feifei; Li, Xiao; Sun, Shuohuan; Song, Shouyang; Li, Tao; Zhu, Qiang; Ren, Wanhua; Qin, Chengyong; et al.
Abstract : Muscle RING‐finger (MuRF) proteins are E3 ubiquitin ligases that are expressed in striated muscle. MuRF2 is an important member of this family, but whether it is expressed in tissues other than striated muscle has not been thoroughly elucidated to date. In this study, we determined that MuRF2 is also expressed in other vital organs, including liver, lung, brain, spleen and kidney. Moreover, we show that the level of MuRF2 expression is significantly decreased in hepatic mononuclear cells of mice with lipopolysaccharide (LPS)/d ‐galactosamine‐induced hepatitis and negatively correlated with the serum levels of alanine aminotransferase and aspartate aminotransferase in these mice. Furthermore, the expression of MuRF2 was down‐regulated in RAW264.7 cells activated with LPS but not in cells treated with polyinosinic‐polycytidylic acid (Poly(I:C)) or with lipidosome plus Poly(I:C). We also found that MuRF2 was able to translocate from the cytoplasm to the nucleus in RAW264.7 cells activated with LPS but not in cells treated with Poly(I:C). In addition, we demonstrated that interleukin 6 and tumour necrosis factor α production and macrophage migration were inhibited after MuRF2 was overexpressed in RAW264.7 cells. We further verified that nuclear factor‐κB p65 subunit level was greatly reduced in RAW264.7 macrophage nuclei by gain of function. Taken together, these findings indicate that MuRF2 may rescue LPS‐induced macrophage activation by suppressing the production of proinflammatory cytokines and cell migration. We also identify a novel function of MuRF2 in non‐muscle tissues and cells. Abstract : The muscle RING finger (MuRF) family of proteins are E3 ubiquitin ligases that have previously been thought to be expressed only in striated muscle tissue. In this study, we showed that MuRF2 may weaken lipopolysaccharide‐induced macrophage activation by suppressing the production of proinflammatory cytokines and cell migration. We also demonstrate a new function of MuRF2 in non‐muscle tissues and cells.